Quality Improvement and Defect Control in Food Packaging Industry with DMAIC Approach - Monica Feby Santoso; M. Nushron Ali Mukhtar (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2026)
Low product packaging quality in food products can negatively impact customer satisfaction and company performance. This research aims to improve the packaging quality of Shanghai Atom Peanut products using the Six Sigma method with the DMAIC approach, consisting of Define, Measure, Analyze, Improve, and Control phases. The research identified two main critical to quality factors: nonconforming product weight and poor sealing quality, which together contributed 84.3 % of total defects. Before improvement, several days showed out-of-control data, with 814 defective units out of 6480 inspected. Improvements were implemented using the FMEA method, including product standardization, sensor installation, and enhanced operator supervision. After improvement, defects were reduced to 299 units, and all data points were within control limits. The RPN decreased significantly, with D1 dropping from 336 to 175 and D2 from 294 to 100. A paired T-test confirmed the improvements were statistically significant with a P-Value of 0.001. This shows that the DMAIC approach effectively reduces defects and supports sustainable process control. For future research, evaluating the effectiveness of the Six Sigma approach across various packaging types, such as metallised packaging, carton boxes, and cans, may contribute to the development of a more efficient and market-orientated packaging process.